Demonstrating utility of global system for sharing genetic resources to national policy makers system through local climate change vulnerability analysis - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Piloting activities finished and proven effective. Research results contributed to positve national level policies to participate in globally organized system for conserving and sharing plant genetic resources.